Preparation method and application of boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst
Patent Information
- Application Number
- CN202411881516.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-12-19
AI Technical Summary
Existing technologies are insufficient for efficiently removing antibiotics from water, especially addressing issues of antibiotic accumulation and resistance. Furthermore, biochar catalysts present risks of metal leaching and slow electron transfer rates.
By introducing Co and B elements, a highly graphitized, endogenously calcium-rich, uniformly porous carbon-based catalyst is constructed. Combined with a persulfate system, it promotes the valence state cycle of Co2+/Co3+ and non-radical reactions, thereby achieving efficient removal of antibiotics.
It achieves efficient removal of antibiotics over a wide pH range, with high degradation efficiency, no metal ion leaching, simple operation, low cost, and strong applicability.
Smart Images

Figure CN119701957B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing and applying a boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst, belonging to the fields of environmental catalysis and advanced oxidation technology. Background Technology
[0002] With the extensive use of antibiotics in livestock farming, pharmaceuticals, and other industries, the antibiotic content in water bodies has gradually increased. Once antibiotics enter the aquatic environment, they cannot be completely removed by natural forces, and sewage treatment plants have limited capacity to treat antibiotics. This results in a large accumulation of antibiotics in water bodies, which not only threatens the survival of aquatic plants and animals and causes bacteria to develop drug resistance, but may also return to the human body through the flow of matter and energy in various systems, turning drugs into poisons and endangering human health.
[0003] Persulfate monosulfate (PMS) oxidation is a highly efficient and stable organic matter treatment technology among advanced oxidation technologies. Biochar, as a low-cost material, can help PMS realize its value and has attracted widespread attention in the field of catalysis. However, biochar needs modification to maximize its resource utilization. Doping with highly reactive transition metals is efficient, but the risks of metal leaching and electron transfer rates must be considered. Therefore, finding a good support or constructing an inclusive structure is crucial. In addition to the encapsulation effect of biochar itself, the regulation of its porosity, graphitization, or degree of defects is also essential. In the process of removing organic matter, non-radicals preferentially react with pollutants with electron donor groups compared to free radicals with higher redox potentials, thereby improving the degradation efficiency of the target pollutants and exhibiting resistance to interference from complex aqueous matrices. Typically, highly graphitized catalysts not only accelerate electron transfer but also promote the formation of non-radicals. Therefore, it is of great significance to enable transition metals to participate in the construction of catalyst structures, making them easy to enter but difficult to leave, and accelerating the valence state cycle of metals. Summary of the Invention
[0004] To address the aforementioned technical problems, this invention provides a boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst with abundant active sites, high degree of graphitization, no metal ion leaching, wide applicable pH range, fast electron transfer, anti-interference, and high efficiency in activating PMS, as well as its preparation method and application.
[0005] This invention introduces Co and B elements to construct a highly graphitized, endogenously calcium-rich, uniformly porous, low-cost carbon-based catalyst. Coupled with a persulfate system, it exhibits excellent synergistic adsorption and degradation effects, and the Co and B elements enhance the catalyst's electrochemical performance. Through reversible redox reactions, it promotes the oxidation of Co... 2+ / Co 3+ The valence state cycle accelerates electron transfer between substances, promoting O2. ·- and 1The generation of O2, primarily via a non-radical pathway, enables the efficient removal of electron-rich antibiotics from water. The production process of the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst is characterized by low raw material costs, simple operation, and low energy consumption. This invention avoids the metal leaching problem inherent in metal-doped catalysts. Specifically, by incorporating Co and optimizing the material structure with Bo, as well as regulating the endogenous Ca content through Co and Bo, the Co and Bo elements achieve a tighter bond between Co and the carbon substrate. The resulting catalyst contains a small amount of Co but exhibits significant catalytic activity, demonstrating high efficiency and environmental friendliness. Furthermore, the Co compound broadens the applicable pH range, allowing the catalyst to operate beyond narrow pH conditions and react efficiently even under extreme pH conditions, exhibiting strong stability and versatility. The mechanism of antibiotic degradation by the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst is primarily via a non-radical pathway.
[0006] This invention provides a method for preparing a boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst, using bamboo powder as the main raw material, comprising the following steps: (1) Mix bamboo powder, boric acid, cobalt salt and water in a mass ratio of 5:0.5~1.5:0.1~1:50~100 and use a magnetic stirrer to achieve full impregnation; (2) The modified biomass obtained in step (1) is placed in a tube furnace and pyrolyzed at 400 ~ 600℃ under a nitrogen atmosphere. The biomass is then washed, dried, and ground to obtain a boron-cobalt doped boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst.
[0007] In the above preparation method, preferably, the cobalt salt in step (1) is cobalt nitrate hexahydrate, the magnetic stirring speed is 200~400 rpm, and the immersion time is 5~7 h.
[0008] In the above preparation method, preferably, the pyrolysis time in step (2) is 1 to 3 hours, and the carbon source and calcium source of the catalyst are bamboo powder.
[0009] This invention provides an application of a boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst in the treatment of antibiotic wastewater. By simultaneously adding the catalyst and PMS to the polluted water, highly efficient removal of antibiotics can be achieved. Furthermore, this catalyst can achieve 100% degradation of quinolone antibiotics such as ofloxacin and ciprofloxacin in approximately 30 minutes. The operation is simple and requires no special equipment.
[0010] The innovation of this invention compared to existing technologies lies in the following: This invention provides a method for preparing a boron-cobalt synergistic graphitization calcium-rich carbon-based catalyst. The main raw material for the catalyst is waste bamboo powder, which is abundant and low-cost. Bamboo powder is rich in lignin, cellulose, calcium, magnesium, etc., making it an ideal carbon source for graphitization structures. When modified by impregnation with boric acid and cobalt salts, the relatively small atomic radius of boron allows it to easily enter the carbon lattice and replace sp2 and sp3 structures. Boron doping not only increases the degree of graphitization of the material but also promotes Co... 2+ / Co 3+ The cycling process can optimize the pore structure of the catalyst, increase the specific surface area, and add active sites. Furthermore, boron doping can induce polarization on the carbon surface, thereby promoting electrostatic and ion-π interactions between the material surface and solution ions. Co exhibits higher oxidation activity compared to other transition metals, which can both improve conductivity and broaden the pH range of the catalyst. The boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst prepared from bamboo powder possesses a uniform porous structure, which not only increases the specific surface area, facilitating the adsorption of oxidants and pollutants, but also provides abundant active sites and a stable loading environment.
[0011] The beneficial effects of this invention are: (1) In view of the problems of complex preparation and complicated process of existing catalysts, the present invention adopts a simple impregnation and pyrolysis method to achieve co-doping of heteroatoms and transition metals, and the raw material cost and equipment energy consumption are both economical. (2) This invention utilizes boron and cobalt synergistically to prepare a highly graphitized biochar catalyst, by regulating... 1 The generation and acceleration of electron transfer of O2 enhance the non-radical pathway for pollutant removal, enabling the selective removal of electron-rich organic matter; the mechanism of antibiotic degradation by boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst is mainly based on the non-radical pathway. (3) The boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst in this invention can achieve efficient removal of antibiotics within a wide pH range (3 ~ 11); (4) The boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst in this invention has high electrical conductivity, low electrical resistance, and exhibits a reversible redox reaction (Co). 2+ / Co 3+ (valence cycle).
[0012] (5) The boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst prepared in this invention does not leach metal ions during the application of antibiotic wastewater treatment. Attached Figure Description
[0013] Figure 1 This is a SEM image of the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1 of this invention.
[0014] Figure 2 The images show the XRD patterns of the original bamboo powder biochar (BC) prepared in Comparative Example 1, the boron-doped bamboo powder biochar (B-BC) prepared in Comparative Example 2, the cobalt-doped bamboo powder biochar (Co-BC) prepared in Comparative Example 3, and the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1.
[0015] Figure 3 Raman spectra of the original bamboo powder biochar (BC) prepared in Comparative Example 1, the boron-doped bamboo powder biochar (B-BC) prepared in Comparative Example 2, the cobalt-doped bamboo powder biochar (Co-BC) prepared in Comparative Example 3, and the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1.
[0016] Figure 4 The cyclic voltammetry (CV) curves are shown for the original bamboo powder biochar (BC) prepared in Comparative Example 1, the boron-doped bamboo powder biochar (B-BC) prepared in Comparative Example 2, the cobalt-doped bamboo powder biochar (Co-BC) prepared in Comparative Example 3, and the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1.
[0017] Figure 5 The images show the electrochemical impedance spectroscopy (EIS) spectra of the original bamboo powder biochar (BC) prepared in Comparative Example 1 and the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1.
[0018] Figure 6 The images show the adsorption and degradation effects of the original bamboo powder biochar (BC) prepared in Comparative Example 1, the boron-doped bamboo powder biochar (B-BC) prepared in Comparative Example 2, the cobalt-doped bamboo powder biochar (Co-BC) prepared in Comparative Example 3, and the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1.
[0019] Figure 7 The graph shows the time-degradation efficiency of the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1 of this invention under different pH conditions.
[0020] Figure 8 The graph shows the degradation effect of the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1 of this invention on ciprofloxacin (CIP).
[0021] Figure 9 The time-degradation efficiency diagram of the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1 of this invention under different quencher conditions is shown.
[0022] Figure 10 The figures show the degradation effects of the boron-cobalt synergistic graphitized calcium-rich carbon-based catalysts prepared in Examples 1, 6-9 of this invention. Detailed Implementation
[0023] The present invention will be further illustrated by the following embodiments, but is not limited to the following embodiments. Example 1
[0024] A method for preparing a boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst according to the present invention includes the following steps: (1) Waste bamboo powder was used, washed with anhydrous ethanol and ultrapure water, dried to constant weight, and ground through a 100-mesh sieve.
[0025] (2) Mix bamboo powder, boric acid, cobalt salt and water in a mass ratio of 5:1.5:1:50 and stir at 300 rpm for 6 hours using a magnetic stirrer to achieve full impregnation.
[0026] (3) The above mixture was filtered, dried and ground in sequence, placed in a crucible and wrapped with aluminum foil, and then placed in a tube furnace at 600°C under a nitrogen atmosphere for 2 hours to obtain modified biochar.
[0027] (4) The above biochar was washed with ultrapure water until the filtrate was neutral, dried in an oven, ground and sieved to obtain a boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst, denoted as CoB-BC.
[0028] Comparative Example 1: A method for preparing raw bamboo powder biochar includes the following steps: (1) Waste bamboo powder was used, washed with anhydrous ethanol and ultrapure water, dried to constant weight, and ground through a 100-mesh sieve.
[0029] (2) The above-treated bamboo powder was placed in a crucible and wrapped with aluminum foil. It was then placed in a tube furnace at 600°C under a nitrogen atmosphere for 2 hours to obtain the original bamboo powder biochar, denoted as BC.
[0030] Comparative Example 2: A method for preparing boron-doped bamboo powder biochar includes the following steps: (1) Waste bamboo powder was used, washed with anhydrous ethanol and ultrapure water, dried to constant weight, and ground through a 100-mesh sieve.
[0031] (2) Mix bamboo powder, boric acid and water in a mass ratio of 5:1.5:50 and stir at 300 rpm for 6 hours using a magnetic stirrer to achieve full impregnation.
[0032] (3) The above mixture was filtered, dried and ground in sequence, placed in a crucible and wrapped with aluminum foil, and then placed in a tube furnace at 600°C under a nitrogen atmosphere for 2 hours to obtain modified biochar.
[0033] (4) The above biochar was washed with ultrapure water until the filtrate was neutral, dried in an oven, ground and sieved to obtain boron-doped bamboo powder biochar, denoted as B-BC.
[0034] Comparative Example 3: A method for preparing cobalt-doped bamboo powder biochar includes the following steps: (1) Waste bamboo powder (BC) was used, washed with anhydrous ethanol and ultrapure water, dried to constant weight, and ground through a 100-mesh sieve.
[0035] (2) Mix bamboo powder, cobalt nitrate hexahydrate and water in a mass ratio of 5:1:50 and stir at 300 rpm for 6 hours using a magnetic stirrer to achieve full impregnation.
[0036] (3) The above mixture was filtered, dried and ground in sequence, placed in a crucible and wrapped with aluminum foil, and then placed in a tube furnace at 600°C under a nitrogen atmosphere for 2 hours to obtain modified biochar.
[0037] (4) The above biochar was washed with ultrapure water until the filtrate was neutral, dried in an oven, ground and sieved to obtain cobalt-doped bamboo powder biochar, denoted as Co-BC.
[0038] BET analysis was performed, and BC was measured to be 11.82 m. 2 / g, CoB-BC is 51.98 m 2 / g.
[0039] Figure 1 The images show SEM images (Figures (a) and (b) at different magnifications) of the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1 of this invention. The microstructure of CoB-BC exhibits a rich and uniform pore structure, attributed to the improvement of graphitization by boron and the regulation of defects by cobalt. Consistent with BET results, the specific surface area of CoB-BC increases and the number of reaction sites increases with sufficient modification by boric acid and cobalt nitrate. This is beneficial for the adsorption of PMS and antibiotics by CoB-BC. Simultaneously, adsorption further promotes the contact between substances and electron transfer, thereby promoting degradation. The uniform porous structure of CoB-BC provides a good support for the loading of metal particles, and the encapsulation effect of biochar significantly reduces metal leaching.
[0040] Figure 2The images show the XRD patterns of the original bamboo powder biochar (BC) prepared in Comparative Example 1, the boron-doped bamboo powder biochar (B-BC) prepared in Comparative Example 2, the cobalt-doped bamboo powder biochar (Co-BC) prepared in Comparative Example 3, and the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1. Figure 2 In the study, the high crystallinity of BC itself is clearly observed, due to the abundant calcium in bamboo powder, primarily in the forms of CaCO3 and CaMg(CO3)2. B doping reduces the peak intensity of CaCO3 and CaMg(CO3)2, likely due to the reaction of boric acid with it at high temperatures. Simultaneously, it optimizes the pore structure of the catalyst, increasing the specific surface area and enhancing the material's adsorption performance. Co doping severely disrupts the CaMg(CO3)2 morphology, while potentially slightly increasing CaCO3. When B and Co coexist, B is embedded in the Co lattice, and the absence of a distinct Co structure indicates a low Co content. Under the synergistic effect of B and Co, the overall effect on CaMg(CO3)2 is relatively small. BC exhibits a certain degree of graphitic carbon structure; B slightly promotes graphitization, while Co introduces defects, ultimately resulting in CoB-BC exhibiting a high degree of graphitization.
[0041] Figure 3 Raman spectra of the original bamboo powder biochar (BC) prepared in Comparative Example 1, the boron-doped bamboo powder biochar (B-BC) prepared in Comparative Example 2, the cobalt-doped bamboo powder biochar (Co-BC) prepared in Comparative Example 3, and the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1. Figure 3 The D and G bands in Raman spectroscopy reflect the degree of graphitization of different materials, while the I bands of the four materials... D / I G The values were 0.86, 0.83, 0.89, and 0.85, respectively. BC exhibits a high degree of graphitization, making it an excellent metal support; this property can mitigate the leakage of metal elements. The small atomic radius of B allows it to easily enter the carbon lattice during the modification of raw bamboo powder, substituting for sp2 and sp3 structures and promoting graphitization. Conversely, the introduction of Co introduces more defects, consistent with the XRD results. B and Co work synergistically to construct a CoB-BC with a high degree of graphitization and abundant active sites.
[0042] Figure 4 The CV diagrams are for the original bamboo powder biochar (BC) prepared in Comparative Example 1, the boron-doped bamboo powder biochar (B-BC) prepared in Comparative Example 2, the cobalt-doped bamboo powder biochar (Co-BC) prepared in Comparative Example 3, and the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1. Figure 4The electron transport properties of different materials were distinguished. Based on the current variation, the electron conduction rate followed the order CoB-BC > Co-BC > B-BC > BC. BC, mainly composed of carbon, calcium, and magnesium, has low electrical conductivity. The addition of heteroatoms (B) accelerates the electron transport properties of B-BC due to B's promotion of graphitization. Furthermore, the introduction of metallic Co and non-metallic B results in stronger electrochemical activity. The CV curve of CoB-BC shows obvious redox peaks, indicating a reversible redox reaction, which is attributed to B's promotion of Co valence cycling.
[0043] Figure 5 EIS diagrams of the original bamboo powder biochar (BC) prepared in Comparative Example 1 and the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1 of this invention. Figure 5 The electrical conductivity of the catalysts is determined by comparing the EIS plots of BC and CoB-BC. A smaller slope indicates lower resistivity and higher conductivity. The plot shows that the modification of BC by B and Co accelerates electron transfer efficiency. Since the electron transfer pathway is non-radical, this increases the proportion of non-radical pathways in the pollutant removal mechanism. Example 2
[0044] Comparative Examples 1-3 and Example 1 were applied to the treatment of electron-rich antibiotic wastewater, with ofloxacin as the target pollutant, including the following steps: 50 mg of the original bamboo powder biochar (BC) prepared in Comparative Example 1, the boron-doped bamboo powder biochar (B-BC) prepared in Comparative Example 2, the cobalt-doped bamboo powder biochar (Co-BC) prepared in Comparative Example 3, and the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1 were weighed and added to 100 mL of 10 mg / L ofloxacin solution, respectively, and placed in a shaker for adsorption reaction. Under the above conditions, 1.5 mL of 0.1 M persulfate (PMS) solution was added to each conical flask, and the flasks were placed in a shaker for degradation reaction. Seven samples were taken at 10-minute intervals, each 3 mL, and quenched with 100 μL of sodium thiosulfate. Finally, the ofloxacin concentration was determined by ultraviolet spectrophotometry.
[0045] Figure 6 The graphs show the adsorption and degradation effects of the original bamboo powder biochar (BC) prepared in Comparative Example 1, the boron-doped bamboo powder biochar (B-BC) prepared in Comparative Example 2, the cobalt-doped bamboo powder biochar (Co-BC) prepared in Comparative Example 3, and the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1 (C in the graphs). tThe concentrations of pollutants after degradation are represented by C0, and C0 represents the initial concentration of pollutants. In the figure, the adsorption and degradation effects of BC are both poor. The introduction of B or Co improves both the adsorption and degradation rates of the catalyst, with CoB-BC showing the best removal effect. Boric acid reacts with calcium species in bamboo powder, increasing the specific surface area and improving the pore structure, while also causing polarization of the carbon surface. Co introduces defects, increasing the active sites of the catalyst and thus enhancing the adsorption effect. B itself can cleave the OO bonds of PMS and promote electron transfer and the valence state cycle of Co. Furthermore, Co has high oxidation activity. The synergistic effect of boron, cobalt, and calcium ternary catalysts enables CoB-BC to achieve complete removal of ofloxacin within 40 minutes, and ICP analysis shows no metal ion leaching. Example 3
[0046] The application of boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst in the degradation of electron-rich antibiotic wastewater under different pH conditions, with ofloxacin as the target pollutant, includes the following steps: The control group was kept unadjusted. In the experimental group, the pH of a 10 mg / L ofloxacin solution (100 mL) was pre-adjusted with HCl and NaOH to 3, 5, 7, 9, and 11, respectively. Then, 50 mg of catalyst and 1.5 mL of 0.1 M PMS solution were simultaneously added to an Erlenmeyer flask, and the flask was placed in a shaker at 25°C for degradation. Seven 3 mL samples were taken at 10-minute intervals and quenched with 100 μL of sodium thiosulfate. Finally, the ofloxacin concentration was determined using a UV spectrophotometer.
[0047] Figure 7 This is a time-degradation efficiency graph of the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1 of this invention under different pH conditions. At pH 3-9, the degradation curves almost overlap with the control group curves, indicating that this pH range does not affect the catalyst's degradation efficiency, demonstrating the catalyst's wide pH applicability and stability. At pH 11, the degradation efficiency of ofloxacin decreases slightly under the strongly alkaline environment. This is because pH affects ROS generation and the catalyst's surface charge, but the removal rate still reaches 90%. Example 4
[0048] Example 1 shows its application in treating electron-rich antibiotic wastewater, with ciprofloxacin (CIP) as the target pollutant, and includes the following steps: 50 mg of the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1 was weighed and added to 100 mL of a 10 mg / L ciprofloxacin solution. 1.5 mL of a 0.1 M persulfate (PMS) solution was added to the Erlenmeyer flask, and the mixture was placed in a shaker for degradation. Seven samples (3 mL each) were taken at 10-minute intervals and quenched with 100 μL of sodium thiosulfate. The ciprofloxacin concentration was finally determined using a UV spectrophotometer.
[0049] Figure 8 This image shows the degradation effect of the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1 of this invention on ciprofloxacin (CIP). Similar to the degradation effect on ofloxacin, ciprofloxacin achieved 100% degradation within 30 minutes. This is because ciprofloxacin and ofloxacin both belong to the quinolone class of antibiotics, have similar structures and degradation pathways, and are both electron-rich antibiotics. Under the adsorption and catalysis of CoB-BC, PMS forms a complex with the antibiotic, and CoB-BC acts as a bridge for electron transfer. The electron-rich antibiotic loses electrons and is gradually oxidized. Simultaneously, under the attack of ROS, CoB-BC achieves highly efficient degradation of the antibiotic. Example 5
[0050] The application of boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst in the degradation of electron-rich antibiotic wastewater under different quenching agent conditions, with ofloxacin as the target pollutant, includes the following steps: 50 mg of the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1 was weighed and added to 100 mL of a 10 mg / L ofloxacin solution. 1.5 mL of a 0.1 M persulfate (PMS) solution was added to an Erlenmeyer flask. Simultaneously, different concentrations and types of quenchers were added to different Erlenmeyer flasks, and the mixtures were placed in a shaker for degradation reaction. Seven samples (3 mL each) were taken at 10-minute intervals and quenched with 100 μL of sodium thiosulfate. Finally, the ofloxacin concentration was determined using a UV spectrophotometer.
[0051] Figure 9 This is a time-degradation efficiency graph of the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1 of this invention under different quencher conditions. Methanol (MeOH) was used to quench sulfate radicals (SO42-). ·- ) and hydroxyl radicals (·OH), tert-butanol (TBA) can quench ·OH, L-histidine and furfuryl alcohol (FFA) target singlet oxygen ( 1 O2), p-benzoquinone (PBQ) can quench superoxide radicals (O2). ·-When MeOH and TBA concentrations were 10 mM and 50 mM, their inhibitory effect on the reaction system was minimal, indicating that SO42-... ·- ·OH is not primarily ROS; when L-histidine and FFA concentrations are 5 mM and 10 mM, the degradation rate of ofloxacin is almost zero, and the reaction process is completely inhibited, indicating that... 1 O2 plays a major role in the degradation process, indicating that the non-radical pathway is the main degradation route in the reaction system, which is consistent with the applicability of CoB-BC to a wide pH range of 3-11. The slight inhibition of degradation by PBQ indicates the presence of O2 in the reaction process. ·- Research shows that O2 ·- It can be converted into 1 O2 further highlights 1 The importance of O2. Example 6
[0052] A method for preparing a boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst according to the present invention includes the following steps: (1) Waste bamboo powder was used, washed with anhydrous ethanol and ultrapure water, dried to constant weight, and ground through a 100-mesh sieve.
[0053] (2) Mix bamboo powder, boric acid, cobalt salt and water in a mass ratio of 5:0.5:1:50 and stir at 300 rpm for 6 hours using a magnetic stirrer to achieve full impregnation.
[0054] (3) The above mixture was filtered, dried and ground in sequence, placed in a crucible and wrapped with aluminum foil, and then placed in a tube furnace at 600°C under a nitrogen atmosphere for 2 hours to obtain modified biochar.
[0055] (4) The above biochar was washed with ultrapure water until the filtrate was neutral, dried in an oven, ground, and sieved to obtain a boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst, denoted as CoB. 0.5 -BC. Example 7
[0056] A method for preparing a boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst according to the present invention includes the following steps: (1) Waste bamboo powder was used, washed with anhydrous ethanol and ultrapure water, dried to constant weight, and ground through a 100-mesh sieve.
[0057] (2) Mix bamboo powder, boric acid, cobalt salt and water in a mass ratio of 5:1:1:50 and stir at 300 rpm for 6 hours using a magnetic stirrer to achieve full impregnation.
[0058] (3) The above mixture was filtered, dried and ground in sequence, placed in a crucible and wrapped with aluminum foil, and then placed in a tube furnace at 600°C under a nitrogen atmosphere for 2 hours to obtain modified biochar.
[0059] (4) The above biochar was washed with ultrapure water until the filtrate was neutral, dried in an oven, ground and sieved to obtain a boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst, denoted as CoB1-BC. Example 8
[0060] A method for preparing a boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst according to the present invention includes the following steps: (1) Waste bamboo powder was used, washed with anhydrous ethanol and ultrapure water, dried to constant weight, and ground through a 100-mesh sieve.
[0061] (2) Mix bamboo powder, boric acid, cobalt salt and water in a mass ratio of 5:1.5:0.1:50 and stir at 300 rpm for 6 hours using a magnetic stirrer to achieve full impregnation.
[0062] (3) The above mixture was filtered, dried and ground in sequence, placed in a crucible and wrapped with aluminum foil, and then placed in a tube furnace at 600°C under a nitrogen atmosphere for 2 hours to obtain modified biochar.
[0063] (4) The above biochar was washed with ultrapure water until the filtrate was neutral, dried in an oven, ground, and sieved to obtain a boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst, denoted as Co. 0.1 B-BC. Example 9
[0064] A method for preparing a boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst according to the present invention includes the following steps: (1) Waste bamboo powder was used, washed with anhydrous ethanol and ultrapure water, dried to constant weight, and ground through a 100-mesh sieve.
[0065] (2) Mix bamboo powder, boric acid, cobalt salt and water in a mass ratio of 5:1.5:0.5:50 and stir at 300 rpm for 6 hours using a magnetic stirrer to achieve full impregnation.
[0066] (3) The above mixture was filtered, dried and ground in sequence, placed in a crucible and wrapped with aluminum foil, and then placed in a tube furnace at 600°C under a nitrogen atmosphere for 2 hours to obtain modified biochar.
[0067] (4) The above biochar was washed with ultrapure water until the filtrate was neutral, dried in an oven, ground, and sieved to obtain a boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst, denoted as Co. 0.5 B-BC.
[0068] Figure 10 The figures show the degradation effects of the boron-cobalt synergistic graphitized calcium-rich carbon-based catalysts prepared in Examples 1 and 6-9 of this invention. As can be seen from the figures, within a given range, the overall performance of the catalysts prepared with different mass ratios tends to be consistent. They exhibit rapid degradation of ofloxacin, with degradation rates approaching 90% at 10 min, and gradually stabilizing after 30 min. Figure 10 This reflects that within a certain mass ratio range, highly efficient catalysts can be successfully prepared. However, the degradation performance of catalysts prepared with different ratios still differs, with the CoB-BC prepared in Example 1 showing the best degradation effect.
Claims
1. The application of a boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst in the treatment of antibiotic wastewater, characterized in that, The simultaneous addition of a catalyst and PMS to antibiotic wastewater achieves highly efficient removal of antibiotics; the catalyst achieves 100% degradation of quinolone antibiotics within 30 minutes; and no metal ion leaching occurs. The preparation method of the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst includes the following steps: (1) Mix bamboo powder, boric acid, cobalt salt and water in a mass ratio of 5:0.5~1.5:0.1~1:50~100 and use a magnetic stirrer to achieve full impregnation; the magnetic stirring speed is 200~400rpm and the impregnation time is 5~7h; bamboo powder contains abundant calcium, which is mainly in the form of CaCO3 and CaMg(CO3)2; (2) The modified biomass obtained in step (1) is placed in a tube furnace and pyrolyzed at 400 ~ 600℃ under a nitrogen atmosphere. The biomass is then washed, dried, and ground to obtain a boron-cobalt doped boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst.
2. The application of the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst according to claim 1 in the treatment of antibiotic wastewater, characterized in that: In step (1), the cobalt salt is cobalt nitrate hexahydrate.
3. The application of the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst according to claim 1 in the treatment of antibiotic wastewater, characterized in that: The pyrolysis time in step (2) is 1 to 3 hours.
Citation Information
Patent Citations
Preparation method of biochar-supported cobaltosic oxide catalytic material
CN111013590A
3D catalyst for catalytic degradation of organic pollutants as well as preparation and application of 3D catalyst
CN111408373A
Method for preparing boron-doped porous carbon material with high specific surface area from biomass
CN111994907A
Cobalt-boron co-doped carbon nitride catalyst and preparation method thereof
CN116212930A
